Knowledge, attitude and health beliefs on cervical cancer screening in Ajumako-Eyan-Essiam District, Ghana - Sampson, Charlotte Naa (Can Oncol Nurs J, 2021)
The study assessed women in Ajumako-Eyan-Essiam District (AEED) on knowledge, attitude, and health beliefs on cervical cancer screening. In Ghana, cervical cancer ranks as the second leading cause of female cancers. In clinical practice and studies done on women with cervical cancer, early diagnosis, treatment, and prevention of cervical cancer is widely influenced by women’s knowledge, and attitude towards screening, yet there is no study on knowledge, attitude, and health beliefs among women in AEED. A quantitative cross-sectional design was used, with a descriptive statistical analysis of data from 240 women. The results showed that 61.3% of women do not know which organs cervical cancer affects or when to follow up after a normal smear, which might suggest some deficit in their level of knowledge. Thirty-six percent believed that the Pap test is done once and 57.1% were of the view that it is expensive, which limits patronage. The majority of respondents refused to go for screening for fear of the unknown (48.8%) while others believed that they might not be at risk (65.8%). A significant number (46.7%) were of the view that cervical cancer cannot be cured. In conclusion, the inadequate knowledge and false health beliefs of women influenced their attitude toward cervical cancer screening.